The Association of SGLT-2 inhibitors (Empagliflozin) with the development of hypernatremic dehydration: a case report - Diana Alegre-González; Sandra García-Guerreros; Sara Martínez-Hernández; Ana Yasmina Brito-Díaz; Marta Casañas-Martínez; Ramón Baeza-Trinidad (Iberoamerican Journal of Medicine)
Sodium-Glucose-Cotransporter -2 inhibitors (SGLT2 inhibitors) are a new class of drugs that reduce blood glucose levels by increasing glucose excretion and lowering blood pressure through natriuresis and plasma volumen contraction. Due to their beneficial effects, they are currently used in treatment of both diabetes mellitus and heart failure, leading to widespread use in recent years. Here, we present a case of a patient who experienced severe hypernatremic dehydration related to the initiation of treatment with iSGLT2 inhibitors.